2016
DOI: 10.1103/physrevlett.116.221101
|View full text |Cite|
|
Sign up to set email alerts
|

Tests of General Relativity with GW150914

Abstract: The LIGO detection of GW150914 provides an unprecedented opportunity to study the two-body motion of a compact-object binary in the large-velocity, highly nonlinear regime, and to witness the final merger of the binary and the excitation of uniquely relativistic modes of the gravitational field. We carry out several investigations to determine whether GW150914 is consistent with a binary black-hole merger in general relativity. We find that the final remnant's mass and spin, as determined from the low-frequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

63
1,699
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,729 publications
(1,787 citation statements)
references
References 101 publications
63
1,699
4
1
Order By: Relevance
“…Several tests of general relativity were performed using GW150914, as described in Ref. [41]. One of these was a parametrized test for the consistency of the observed waveform with a general-relativity-based model.…”
Section: Introductionmentioning
confidence: 99%
“…Several tests of general relativity were performed using GW150914, as described in Ref. [41]. One of these was a parametrized test for the consistency of the observed waveform with a general-relativity-based model.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of black holes are undergoing a revolution, with the advent of gravitational wave astronomy [2][3][4][5] and the promise of very-longbaseline radio observations of supermassive black holes by the Event Horizon Telescope [6,7]. While black holes are consistent with all electromagnetic and gravitational wave observations to date [4,5,[8][9][10], no experiment has been able probe spacetime near the event horizon [11][12][13]. Moreover, the event horizon is at the heart of the BH information paradox [14], and the role of black holes in a quantum theory of gravity is an open question.…”
Section: Introductionmentioning
confidence: 96%
“…i.e. it is important to keep in mind that in addition, [20] has confirmed that a subsequent analysis of the event GW150914 by the LSC constrained the graviton Compton wavelength of those alternative theories of gravity in which the graviton is massive and placed a level of 90% confidence on the lower bound of 10 13 km for a Compton wavelength of the graviton. Doing this sort of vetting protocols in line with being consistent with investigation as to a real investigation as to the fundamental nature of gravity.…”
Section: Discussionmentioning
confidence: 89%